Dimensión psicosexual: una definición desde el autoconocimiento, realidades y placer (2024)
The purpose of this research was to analyze which were the factors that influence the psychosexual dimension from the self-knowledge, realities and pleasure, which was carried out at the Antonio Nariño University, located in the municipality of Roldanillo, Valle del Cauca; by means of a mixed type study, concurrent triangulation design, explanatory scope and a multilevel sample for mixed methods formed by (36) people for the quantitative methodology and 12% of this population, that is (6) people for the qualitative methodology. The data collected were processed and analyzed through tabulation with Likert scaling and a triangulation matrix. The results of the research expose the areas of greater ignorance of sexuality and the sociocultural influence in their personal constructions. In the application of instruments, discomfort is evidenced in the face of questions posed in the questionnaire and in the interview, thus recognizing the emotions experienced when talking about psychosexual development. It was concluded that the lack of knowledge about sexual norms has a significant influence on sexual realities, pleasure and health.